Measurements of the pseudorapidity dependence of the total transverse energy in proton-proton collisions at $\sqrt{s}=7$ TeV with ATLAS - ATLAS collaboration (2889 authors); Aguilar-Saavedra, Juan Antonio; Anjos, Nuno; Cantrill, Robert; Carvalho, João; Castro, Nuno Filipe; Conde Muiño, Patricia; Da Cunha Sargedas De Sousa, Mario Jose; Do Valle Wemans, André; Fiolhais, Miguel; Gomes, Agostinho; Gonçalo, Ricardo; et al. (My University, 2012)
This paper describes measurements of the sum of the transverse energy of particles as a function of particle pseudorapidity, eta, in proton-proton collisions at a centre-of-mass energy, sqrt(s) = 7 TeV using the ATLAS detector at the Large Hadron Collider. The measurements are performed in the region |eta| < 4.8 for two event classes: those requiring the presence of particles with a low transverse momentum and those requiring particles with a significant transverse momentum. In the second dataset measurements are made in the region transverse to the hard scatter. The distributions are compared to the predictions of various Monte Carlo event generators, which generally tend to underestimate the amount of transverse energy at high |eta|.